Vacuum glazing for highly insulating windows: Recent developments and future prospects. (February 2016) - Cuce, Erdem; Cuce, Pinar Mert
Abstract: A comprehensive review of vacuum glazing technology from state-of-the-art developments to future prospects has been presented. The review has been conducted in a thematic way in order to allow an easier comparison, discussion and evaluation of the findings. First, a thorough overview of historical development of vacuum glazing has been given. Then, numerous experimental, theoretical, numerical and simulation works on the scope have been evaluated and the characteristic results from the said works have been analyzed. Commercial vacuum glazing products in market have been assessed in terms of several performance parameters such as overall heat transfer coefficient, visible light transmittance, solar heat gain coefficient and cost. Techno-economic and environmental aspects of vacuum glazing technology have also been discussed. It can be concluded from the results that overall heat transfer coefficient of a vacuum glazing can be reduced up to 0.20 W/m 2 K through optimized integrations with low-e coatings. The incomparable U -value range of vacuum glazing enables significant mitigation in energy consumption levels and greenhouse gas emissions. Retrofitting 25.6 million homes in the UK with vacuum glazing can provide a carbon abatement of about 40 million tonnes a year, which is very promising.